2010
DOI: 10.1016/b978-0-12-385032-4.00003-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Kaposi's Sarcoma-associated Herpesvirus and Related Oncogenesis

Abstract: Kaposi’s sarcoma herpesvirus (KSHV), also known as human herpesvirus 8 (HHV-8), is the most recently identified human tumor virus, and is associated with the pathogenesis of Kaposi’s sarcoma and two lymphoproliferative disorders known to occur frequently in AIDS patients—primary effusion lymphoma and multicentric Castleman disease. In the 15 years since its discovery, intense studies have demonstrated an etiologic role for KSHV in the development of these malignancies. Here, we review the recent advances linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
128
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 385 publications
(473 reference statements)
0
128
0
3
Order By: Relevance
“…This finding, coupled with the higher prevalence of OtHV-1 in the genital tract, led the authors to suggest that the virus is sexually transmitted and that there was similarity between the epidemiology of OtHV-1 infection in CSL and HHV-8 in humans [61]. Studies into the epidemiology of HHV-8 have suggested that sexual activity plays an important role in the transmission of the virus [62], particularly in the case of AIDS-associated Kaposi's sarcoma [63,64].…”
Section: (D) Infectious Diseasementioning
confidence: 99%
“…This finding, coupled with the higher prevalence of OtHV-1 in the genital tract, led the authors to suggest that the virus is sexually transmitted and that there was similarity between the epidemiology of OtHV-1 infection in CSL and HHV-8 in humans [61]. Studies into the epidemiology of HHV-8 have suggested that sexual activity plays an important role in the transmission of the virus [62], particularly in the case of AIDS-associated Kaposi's sarcoma [63,64].…”
Section: (D) Infectious Diseasementioning
confidence: 99%
“…Th is may indicate that M4 gene can be in some level, directly or indirectly, involved in oncogenic processes, as hypothesized before (6). On the other hand, MHV-60 with signifi cantly higher oncogenic potential (22%) than MHV-68 (9%) (10, 11) had present identical set of genes (M1-M4) in studied region which may suggest that oncogenic process is most likely driven and facilitated by more than one gene product, as evidenced also during EBV-and KSHV-tumorigenesis (2,4). Sequence diff erences among various virus stocks of isolates MHV-72 and MHV-76 was unexpected, because the primary source of particular isolates was common.…”
mentioning
confidence: 63%
“…To avoid the redundancy, we will focus and highlight how viral phosphorylation manipulates production of cytokine through targeting JAK-STAT pathway (Figure 3). In addition to the IFN-associated JAK-STAT pathway, KSHV and EBV have been found to evade the immune response through expressing their own cytokines like vIL-6 and vIL10, respectively (Cai et al, 2010b;Cousins and Nicholas, 2013). …”
Section: Virus Induces Cytokines Via Phosphorylationmediated Activatimentioning
confidence: 99%
“…By using the different binding receptor from the cellular homolog, vIL-6 could activate tyrosine phosphorylation of STAT3 via gp130-associated JAK pathways and MAPK serine/threonine kinase pathways (Cai et al, 2010b;Cousins and Nicholas, 2013). Meanwhile, the phosphorylation levels of STAT3 influence viral lytic reactivation in cell culture (Reddy et al, 2016).…”
Section: Virus Induces Cytokines Via Phosphorylationmediated Activatimentioning
confidence: 99%